In the mood of the other: emotional contagion, empathic knowledge, and intuitive diagnosis in psychiatry - Altobrando, Andrea; Zaninotto, Leonardo (Frontiers in Psychology, 2025)
In this study we critically examine the phenomenological foundations of intuitive diagnosis in Psychiatry by integrating Max Scheler’s concept of emotional contagion with Edith Stein’s three-stage model of empathy. We argue that what Scheler calls emotional contagion offers a useful pre-reflective, bodily-affective resonance that precedes and facilitates deeper empathic understanding of the subject’s experience. Then, we suggest that Stein’s analysis of empathy, which is based on a three-step process—i.e., the emergence of the other’s experience, its imaginative explication, and the final comprehensive objectification—may account for the role of imaginative empathic immersion in diagnostic assessment. This imaginative engagement, grounded in bodily co-originality, allows clinicians to apprehend the subject’s world beyond mere perceptual awareness. We contend that Scheler’s emotional contagion and Stein’s model of empathy can be productively harnessed within a comprehensive diagnostic framework to provide a raw intuitive and imaginative substrate for further cognitive elaboration.